ANALYSIS OF LEAD CONTENT (Pb) IN WASTE STREAMS AND WELL WATER AND PUBLIC HEALTH COMPLAINTS AROUND THE PAPER INDUSTRY IN BONDOWOSO - Balgis Putri Salindra; Prehatin Trirahayu Ningrum; Yunus Ariyanto (Universitas Medan Area, 2022)
Wastewater in an industry which is often called liquid waste is a by-product produced by several human activities. Liquid waste pollution from industrial effluents containing lead (Pb) in dug well water used by the community for daily needs can cause poisoning and health complaints. This study aims to determine the content of lead (Pb) in the liquid waste stream and well water as well as public health complaints around the pulp and paper industry. This type of research was descriptive with the observational method. Liquid waste from the paper and pulp industry is known to contain heavy metal type lead (Pb), if it pollutes the environment around the industry it can cause various negative impacts for the community. There were 2 samples of dug well water 90 meters that have lead content above the quality standard, namely in well 8 and well 10 with lead content of 2,998 mg/L and 4,247 mg/L while for other dug well water it did not exceed the threshold value with results below 0.0085 mg/L. Based on the results of interviews with 40 respondents, most of the respondents who used dug well 8 and well 10 water experienced health complaints such as skin redness and itching on the hands and arms, and the most experienced redness, itching, and hot eyes after using dug well water contaminated with lead (Pb).